Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
Simplifying
3x + 4 = 9x + -8
Reorder the terms:
4 + 3x = 9x + -8
Reorder the terms:
4 + 3x = -8 + 9x
Solving
4 + 3x = -8 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
4 + 3x + -9x = -8 + 9x + -9x
Combine like terms: 3x + -9x = -6x
4 + -6x = -8 + 9x + -9x
Combine like terms: 9x + -9x = 0
4 + -6x = -8 + 0
4 + -6x = -8
Add '-4' to each side of the equation.
4 + -4 + -6x = -8 + -4
Combine like terms: 4 + -4 = 0
0 + -6x = -8 + -4
-6x = -8 + -4
Combine like terms: -8 + -4 = -12
-6x = -12
Divide each side by '-6'.
x = 2
Simplifying
x = 2
God bless you “and I hope this helps”.
Simplifying
3x + 4 = 9x + -8
Reorder the terms:
4 + 3x = 9x + -8
Reorder the terms:
4 + 3x = -8 + 9x
Solving
4 + 3x = -8 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
4 + 3x + -9x = -8 + 9x + -9x
Combine like terms: 3x + -9x = -6x
4 + -6x = -8 + 9x + -9x
Combine like terms: 9x + -9x = 0
4 + -6x = -8 + 0
4 + -6x = -8
Add '-4' to each side of the equation.
4 + -4 + -6x = -8 + -4
Combine like terms: 4 + -4 = 0
0 + -6x = -8 + -4
-6x = -8 + -4
Combine like terms: -8 + -4 = -12
-6x = -12
Divide each side by '-6'.
x = 2
Simplifying
x = 2
God bless you “and I hope this helps”.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.